On instantaneous invariants in dual Lorentzian space kinematics - Ayyildiz, N.; Yalçin, Ș.N. (Archives of Mechanics, 2010)
In this work, we study the concepts of canonical systems and instantaneous invariants in dual Lorentzian space. It gives a systematic approximation about determining the instantaneous invariants. Important for the characterization of higher-order intrinsic properties of a ruled surface, the instantaneous invariants are derived on the basis of line coordinates.